MENINGKATKAN MOTIVASI MELALUI AUDIOVISUAL DALAM PEMBELAJARAN MUSIK DI SMP NEGERI 4 PADANG - Reni Febriyenti; Tulus Handra Kadir; Jagar Lumban Toruan (FBS Universitas Negeri Padang, 2012)
This study aims to discover and describe about how to increase student motivation through the use of audiovisual media in particular subjects Culture Art Art Traditional Music archipelago. This research is descriptive qualitative approach. Collecting data in the field is done by literature study, observations, and interviews to students free of SMP Negeri 4 Padang. Data were collected from two sources, namely data from the literature and from the field, the real situation of learning the art of traditional music in class Nusantara VIII SMP Negeri 4 Padang. The results stated that before the Cultural Arts subject teachers using audiovisual media as a tool in the learning process, the students did not show any motivation in learning art. This is evident from the relatively low participation during the learning process. Many students are not concentrating and not 'care' in the subject described by their teachers, and even many of those who make